Aspek Hukum Kesiapsiagaan dan Penanganan Darurat oleh Unit Penjinakan Bom Satuan Brimob Polda Sumatera Utara dalam Perspektif Hukum Humaniter - Andriyan Mauriz Hans Purba; Halimatul Maryani (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
The threat of terrorism involving the use of explosives poses a serious challenge to Indonesia’s national security, particularly in strategic regions such as North Sumatra. The suicide bombing incident at the Medan Police Headquarters in 2018 serves as a clear example of the urgency of preparedness and emergency response by the Bomb Disposal Unit (JIBOM) of the Brimob Unit at the North Sumatra Regional Police. Handling such situations requires not only high-level technical expertise but must also adhere to the principles of International Humanitarian Law (IHL) to ensure the protection of civilians. This study aims to examine the preparedness of the JIBOM Unit, assess emergency handling procedures for explosive threats based on national regulations, and analyze the conformity of these actions with the principles of humanitarian law. The research uses a normative and empirical juridical approach through literature review, field observation, and interviews with JIBOM personnel. The findings reveal that the JIBOM Unit has implemented an effective preparedness system through regular training, the use of modern technologies such as EOD robots and X-ray scanners, and the application of an integrated command system. Emergency handling procedures are carried out in accordance with police standard operating procedures (SOP) while prioritizing civilian safety. From a legal standpoint, JIBOM's actions align with key humanitarian principles such as distinction, proportionality, humanity, and military necessity, even though Indonesia is not in an armed conflict. This study emphasizes the importance of strengthening regulations, enhancing inter-agency coordination, and improving public literacy to support the lawful and humane execution of bomb disposal operations.